Approaches to nutrition intervention in plaque psoriasis, a multi‐system inflammatory disease—The Diet and Psoriasis Project (DIEPP). Issue 4 (9th September 2022) - Zanesco, Sylvia; Hall, Wendy; Gibson, Rachel; Griffiths, Christopher; Maruthappu, Thiviyani
Abstract: Psoriasis is an immune‐mediated inflammatory skin disease affecting approximately 2% of the UK population. Its pathogenesis is suggested to be an outcome of genetic and environmental interplay. People with psoriasis have an increased likelihood of developing other conditions such as type 2 diabetes and cardiovascular disease. Systemic inflammation is hypothesised to be the common link between psoriasis and cardio‐metabolic diseases. Emerging evidence shows diet as a potential therapeutic adjunct in the management of psoriasis. The Diet and Psoriasis Project ( DIEPP ) aims to investigate whether dietary factors are related to psoriasis severity by conducting an observational study followed by a dietary intervention trial, to assess the effect of the Mediterranean diet (MedD) and time‐restricted eating (TRE) on psoriasis. This review article will explore the potential mechanisms by which the MedD and TRE may exert protective effects on psoriasis, evaluate the current evidence, and outline the design of the DIEPP. Given the early‐stage evidence, we hope to be able to build knowledge to derive medically approved dietary recommendations and contribute to the research gaps exploring the role of diet and psoriasis.